2021
DOI: 10.1038/s41467-020-20581-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive suppression of essential tremor via phase-locked disruption of its temporal coherence

Abstract: Aberrant neural oscillations hallmark numerous brain disorders. Here, we first report a method to track the phase of neural oscillations in real-time via endpoint-corrected Hilbert transform (ecHT) that mitigates the characteristic Gibbs distortion. We then used ecHT to show that the aberrant neural oscillation that hallmarks essential tremor (ET) syndrome, the most common adult movement disorder, can be transiently suppressed via transcranial electrical stimulation of the cerebellum phase-locked to the tremor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 60 publications
4
113
2
Order By: Relevance
“…Another new interventional strategy that may, in the future, be integrated into tremor treatment is the phase-locked suppression of aberrant neural tremor oscillation. Lately, this has been tested via transcranial electrical stimulation of the cerebellum [170], but it would also be suitable for an implanted device. The mechanism behind this innovative strategy is the active disruption of tremor oscillation generation in the olivocerebellar loop, targeting the temporal coherence of the pathology, rather than masking tremor oscillation by desynchronizing firing patterns in the thalamocortical loop as with DBS.…”
Section: Coordinated Reset Dbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another new interventional strategy that may, in the future, be integrated into tremor treatment is the phase-locked suppression of aberrant neural tremor oscillation. Lately, this has been tested via transcranial electrical stimulation of the cerebellum [170], but it would also be suitable for an implanted device. The mechanism behind this innovative strategy is the active disruption of tremor oscillation generation in the olivocerebellar loop, targeting the temporal coherence of the pathology, rather than masking tremor oscillation by desynchronizing firing patterns in the thalamocortical loop as with DBS.…”
Section: Coordinated Reset Dbsmentioning
confidence: 99%
“…The mechanism behind this innovative strategy is the active disruption of tremor oscillation generation in the olivocerebellar loop, targeting the temporal coherence of the pathology, rather than masking tremor oscillation by desynchronizing firing patterns in the thalamocortical loop as with DBS. Schreglmann et al showed that this strategy could effectively suppress tremor during and shortly after stimulation [170]. Nevertheless, future studies are needed to further study the tremor suppression characteristics and determine the safety profile.…”
Section: Coordinated Reset Dbsmentioning
confidence: 99%
“…Differently from DBS (40), in PD tACS had a positive effect on tremor amplitude, maybe because of the different location where stimulation was applied (primary motor cortex instead of basal ganglia). The use of tACS to control tremor in a recent study in ET has also provided potential mechanisms underlying tremor suppression (47). In this study, Schreglmann and colleagues investigated whether cerebellar tACS, phaselocked to tremor oscillation, is able to perturbate synchronous cerebellar activity and disrupt the CTC network oscillations to control ET.…”
Section: Peripheral Biomarkers and Stimulationmentioning
confidence: 99%
“…Further analysis also showed that change in tremor amplitude was associated with a change in temporal coherence, suggesting that stimulation that disrupts the temporal coherence can reduce tremor severity. Using a neurophysiological model of the CTC network under ET condition, the authors suggested that tremor suppression might be related to a timely perturbation of the generation of aberrant complex spikes in the Purkinje cells, therefore disrupting the synchronous activity that generate oscillations in the olivocerebellar loop (47,48).…”
Section: Peripheral Biomarkers and Stimulationmentioning
confidence: 99%
“…We would like to highlight the contribution of a recent work by Schreglmann and colleagues [14] which aimed to suppress the amplitude of essential tremor by applying tACS over the cerebellum, phase-locked to the tremor movement. In this attempt, the authors used a novel strategy called endpoint corrected Hilbert Transform (ecHT) to mitigate the Gibbs phenomenon distortion that produces large errors in the real-time estimation of phase.…”
Section: Dear Editormentioning
confidence: 99%